TESTING SEMI-STRONG FORM MARKET EFFICIENCY: THE CASE OF INDIAN PHARMA SECTORS - Joshi , Janvi; Joshi , Krunal (Indian Journal of Finance and Banking, 2025)
The Efficient Market Hypothesis (EMH) holds that security prices fully reflect all publicly available information, leaving no scope for abnormal gains from fundamental or technical analysis. Despite extensive research, the semi-strong form of EMH remains inconclusive in developing markets. This study examines the degree of semi-strong-form efficiency in the Indian pharmaceutical industry. It explores how effectively the stock prices of leading firms, Sun Pharmaceutical, Dr. Reddy’s Laboratories, Zydus Life Sciences, Cipla, and Torrent Pharmaceuticals, reflect publicly accessible information. The analysis covers five years from 2018–19 to 2022–23 and utilizes the Core Competency Strategic Intent (CCSI) model to assess the relationship between firm fundamentals and market valuation. Tobin’s Q (market value to book value) and employee cost as a percentage of sales are considered representative indicators of valuation and strategic intent. Empirical results show that stock prices in this sector respond more rapidly to short-term, quantifiable factors such as sales performance. In contrast, long-term strategic elements exert a weaker effect on valuation. A numerical evaluation of Tobin’s Q across firms indicates varying degrees of mispricing, suggesting both overvaluation and undervaluation. Overall, the study finds that the Indian pharmaceutical sector exhibits only partial adherence to the semi-strong form of market efficiency, as investors appear to prioritize immediate financial outcomes over comprehensive strategic fundamentals. JEL Classification Codes: G12, G14.